The Book Review of "Qualitative Research Methodology - Mostafa Hamadani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Methodology is one of fundamental lessons in all scientific courses. In recent decades, qualitative methods of research attract many researchers' attention, but unfortunately, the share of academic texts in this new found field is rare. "Qualitative Research Methodology" by Iman has many privileges and numerous initiatives and can compensate shortage of qualitative research methodology to some extent. Nevertheless, there are some formal, structural, and content shortcomings in this book. Utilizing a documentary method,  this study recommends some modifications of organized cases and explains (a) many existing problems, (b) the necessity of formal and content edition of the book especially some diagrams, and models. This study tries to criticize the above-mentioned book and proposes some modifications. Furthermore, of this study's achievements are (a) presentation of logical structure according to Aristotle's division and (b) presentation of its application in the structural review of the book.